2011
DOI: 10.1371/journal.pone.0025438
|View full text |Cite|
|
Sign up to set email alerts
|

MMP-10/Stromelysin-2 Promotes Invasion of Head and Neck Cancer

Abstract: BackgroundPeriostin, IFN-induced transmembrane protein 1 (IFITM1) and Wingless-type MMTV integration site family, member 5B (Wnt-5b) were previously identified as the invasion promoted genes of head and neck squamous cell carcinoma (HNSCC) by comparing the gene expression profiles between parent and a highly invasive clone. We have previously reported that Periostin and IFITM1 promoted the invasion of HNSCC cells. Here we demonstrated that Wnt-5b overexpression promoted the invasion of HNSCC cells. Moreover, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 45 publications
3
85
2
Order By: Relevance
“…MMP9 has also been implicated in the invasion and metastasis of head and neck squamous cell carcinoma (9). Knockout of MMP9 leads to reduced skin and pancreatic carcinogenesis and metastasis, showing delayed tumor vascularization (9)(10)(11). In the present study, the prognostic value of MMP9 in glioma was investigated.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…MMP9 has also been implicated in the invasion and metastasis of head and neck squamous cell carcinoma (9). Knockout of MMP9 leads to reduced skin and pancreatic carcinogenesis and metastasis, showing delayed tumor vascularization (9)(10)(11). In the present study, the prognostic value of MMP9 in glioma was investigated.…”
Section: Discussionmentioning
confidence: 91%
“…Previous meta-analysis has shown a significant correlation between high expression levels of MMP9 and poor prognosis in gastric cancer (18), breast cancer (19), non-small cell lung cancer (20) and colorectal cancer (21). MMP9 has also been implicated in the invasion and metastasis of head and neck squamous cell carcinoma (9). Knockout of MMP9 leads to reduced skin and pancreatic carcinogenesis and metastasis, showing delayed tumor vascularization (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-10 plays an important role in the invasion and metastasis of head and neck squamous cell carcinoma [41] but its role on breast cancer is largely unknown. We found that MMP-10 expression was decreased in comparison with control suggesting that MMP-10 could act as tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…64,65 Wingless-type MMTV integration site family member 5B (WNT5B) knockdown suppresses MMP-10 production and invasion indicating that the WNT signaling pathways can also contribute to invasion. 66,67 Transforming growth factor b (TGFb) can be produced by tumor-associated fibroblasts 68 and induce NF-jB activation 69 and SMAD-dependent MMP production, 70 as well as epithelial to mesenchymal transition (EMT) factors, such as Snail and Slug. [71][72][73][74][75][76] Invasion is stimulated by hypoxia in a Notch-dependent fashion.…”
Section: Cell Surface Receptors Influence Invasivementioning
confidence: 99%
“…100,[115][116][117] Although the mechanism is unclear, EMMPRIN homophilic binding induces the expression of a number of proteases, including MMPs, cathepsin B, and urokinase plasminogen activator receptor (uPAR). 100,115,117,118 Other proteases that have been shown to contribute to HNSCC invasion include MMP-10, 66 MMP-13, 80 matriptase, 119 fibroblast activation protein, 120 and uPA/ uPAR, 117,[121][122][123][124] as well as the glycosidase heparanase.…”
mentioning
confidence: 99%